2022
DOI: 10.3389/fimmu.2022.869018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mitochondrial Antibody Titers Decrease Over Time in Primary Biliary Cholangitis Patients With Ursodeoxycholic Acid Therapeutic Response: A Cohort Study Followed Up to 28 Years

Abstract: BackgroundHow anti-mitochondrial antibody (AMA) and liver biochemistry levels change in primary biliary cholangitis (PBC) patients treated with ursodeoxycholic acid (UDCA) remains unclear.MethodsA 28-year cohort of 157 PBC patients was conducted. Patients with alkaline phosphatase (Alk-p) levels >1.67 × upper limit of normal after 1 year of UDCA treatment were considered nonresponders.ResultsAt baseline, of 157 (mean age: 54.41 years), 136 (86.6%) were female, 51 (32.5%) had cirrhosis, and 128 (81.5%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…[14] In a 28-year cohort study, UDCA responders exhibited decreased AMA IgG titers at 1 year after treatment, which persisted until the last follow-up. [10] Our study also found that AMA was independently associated with the development of cirrhosis in PBC patients. Additionally, higher AMA titers were linked to an increased risk of developing liver cirrhosis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[14] In a 28-year cohort study, UDCA responders exhibited decreased AMA IgG titers at 1 year after treatment, which persisted until the last follow-up. [10] Our study also found that AMA was independently associated with the development of cirrhosis in PBC patients. Additionally, higher AMA titers were linked to an increased risk of developing liver cirrhosis.…”
Section: Discussionsupporting
confidence: 73%
“…[7] Nevertheless, accumulating evidence suggests that AMA titers may be associated with the outcome of PBC patients. [8][9][10] Currently, there is still controversy regarding the relationship between AMA and prognosis for PBC patients. Accordingly, we conducted a retrospective study to investigate the association between AMA and liver cirrhosis in PBC patients and to establish the relationship between AMA and different stages of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…First, patients with mild PBC might not have been enrolled due to lack of alertness of clinicians to register them with the ICD‐9 code. Second, the fact that the TNHIRD did not contain clinical findings, direct laboratory results, or pathological results 60 . and that UDCA is not specific for PBC treatment, might have biased the data to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the fact that the TNHIRD did not contain clinical findings, direct laboratory results, or pathological results. 60 and that UDCA is not specific for PBC treatment, might have biased the data to some extent. Third, the PBC rates might have been underestimated, as patients with HBV or HCV infection had been eliminated.…”
Section: Countries/regionsmentioning
confidence: 99%
“…Moreover, how AMA titers vary according to therapy remains a largely unexplored field, with the only evidence available coming from primary biliary cholangitis: an Asian cohort demonstrated that a decrease of AMA titers was noticed in patients responding to ursodeoxycholic acid therapy, but not in non-responders. 142 …”
Section: Treatmentmentioning
confidence: 99%